Modelling of trans-esterification of waste cooking oil in a batch stirred tank reactor - Adeyemi, Nabeel Adedapo (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
To model the transesterification of waste cooking oil (WCO), the physio-chemical details has been obtained by transesterification of waste cooking oil in a 1-Litre stirred tank reactor (STR) and 2-D Particle Image Velocimetry (PIV) technique. For this study, the L9 Taguchi orthogonal array (OA) design was used to determine the effect of temperature, impeller speed and impeller bottom distance (IBC) on the fatty acid methyl ester (FAME) yield. Single step transesterification with NaOH catalysis was carried out on waste cooking oil (WCO) between 60-70° C due to the low level of FFA. Under the experimental conditions, optimum FAME yield was obtained at 60° C and 70° C, 700 rpm and 25 mm IBC between 5-15 min for 6-blade radial impeller (unbaffled) and 60° C, 700 rpm and 20 mm IBC in 10 min for mixed flow impeller (baffled) in the 1-L STR. The peak yield time, which had not been considered in previous studies, is detailed here. An exponential expression was established to derive FAME yield resulting from a 2nd-order rate model. The work also showed a novel technique based on absorbance spectra and analogue signal to monitor reaction time. The local dissipation rate, mean velocities and turbulent kinetic energy (TKE) in the impeller region of the radial and mixed flow impellers were evaluated via 2-D PIV technique. Large eddy simulation (LES) analogy used to estimate dissipation rate showed even dissipation regime (30 times more than the computed mean dissipation rate in the tank) for mixed flow impeller. Comparison of the PIV data with three turbulent flow models (kappa-epsilon (к-ε), shear stress transport (sst) kappa-omega (к-ω) and Reynold's stress model (RSM)) was carried out at impeller speed between 600 – 700 rpm. The RSM agreed with PIV results while comparing mean, radial and axial velocity, kinetic energy and energy dissipation against the к-ε and sst (к-ω) models at positions below the impeller for the mixed flow impeller. The knowledge of the suitability of the RSM to simulate flow using the mixed-flow impeller is extended here. Subsequently, the transesterification was simulated based on the eddy dissipation model (EDM) incorporating reaction parameters. Mean energy from PIV was used to provide the dissipation/turbulent ratio in the EDM. Based upon a eulerian-eulerian framework, a gradient method was used to obtain FAME yield defined in ANSYS Fluent by special user defined functions (UDF), assuming non-homogenous, statistically isotropic turbulence. The model was able to simulate the reaction for unbaffled 1 and 2-L STR, where the yield was 18 and 23% lesser to experimental result respectively. The model gives a fair comparison of numerical and experimental yields and extends the tools available from modelling transesterification of oil. Taking cognizance of the result, further validation of the developed UDF for large scale tank is suggested to improve the model.